Liquidity Management and Central Bank Strength: Bank of England Operations Reloaded, 1889-1910 - Stefano Ugolini (Norges Bank, 2016)
Is a strong commitment to monetary stability enough to ensure credibility? The recent literature suggests it might not be if the central bank cannot perform pure interest rate policy and has to resort to balance sheet policy: the central bank's financial strength (i.e. the long-term sustainability of its policy) is also a determinant of credibility. This paper provides historical evidence on the issue by focusing on the case of the Bank of England at the heyday of the classical gold standard. It shows that as the Bank was not perceived as having the means to fulfil all of its obligations, the efficacy of its interest rate policy was poor. Failing to reform for political economy reasons, the Bank eventually had to default on its formal convertibility mandate.
hdl:11250/2495719
Keywords: E42; E43; E58; N13; 330; central banking; institutional design; monetary policy implementation; reverse repos; term structure of interest rates; gold standard